Early detection of positive blood cultures by the acridine orange staining technique. - Tierney, B M (1983)
Staining 2,205 macroscopically negative blood cultures with acridine orange after 6 to 17 h of inoculation and incubation was as sensitive as an early subculture in detecting positive blood cultures. Of the 179 positive blood cultures, 30 (16.8%) were detected by acridine orange alone, 19 (10.6%) were detected by early subculture alone, 84 (46.9%) were detected by both techniques, and 46 (25.7%) were not detected by either method. The latter group includes cultures that became positive after 48 h of incubation. Acridine orange staining of smears prepared from macroscopically negative blood cultures after 6 to 17 h is a rapid, reliable method to detect positive blood cultures.